2018
DOI: 10.2334/josnusd.17-0426
|View full text |Cite
|
Sign up to set email alerts
|

Differential dendritic cell responses to cell wall mannan of <i>Candida albicans</i>, <i>Candida parapsilosis</i>, and <i>Candida dubliniensis </i>

Abstract: Mannan (mannosylated glycoproteins) in the outermost layer of the Candida cell wall may be the first molecules that interact with host dendritic cells (DCs) and activate immune responses that determine disease outcomes. However, little is known about how different mannan structures of common oral Candida species affect DC activation. The effects of heat-inactivated (HI) yeast cells and soluble mannan of Candida albicans, Candida parapsilosis, and Candida dubliniensis on bone marrow-derived DC (BMDC) responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…T. rubrum is the major cause of “athlete’s foot”, onychomycosis, and many other persistent skin diseases that affect the quality of life for hundreds of millions of people around the world. , C. albicans is another opportunistic pathogen that causes candidiasis, which commonly occurs in women, young infants, the elderly, and immunocompromised individuals. , Candidiasis affects the normal life of patients and is the cause of mortality in many cases, such as in patients with AIDS or pediatric candidemia . Unfortunately, in the clinic, the treatment of fungal infections using nystatin and amphotericin B has been hindered by the low selectivity of these molecules for the target cells versus the host cells, poor water solubility and, consequently, low absorption and bioavailability. , In this work, we showed that FsC could serve as an active targeting molecule for these pathogenic fungi (Figure and Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…T. rubrum is the major cause of “athlete’s foot”, onychomycosis, and many other persistent skin diseases that affect the quality of life for hundreds of millions of people around the world. , C. albicans is another opportunistic pathogen that causes candidiasis, which commonly occurs in women, young infants, the elderly, and immunocompromised individuals. , Candidiasis affects the normal life of patients and is the cause of mortality in many cases, such as in patients with AIDS or pediatric candidemia . Unfortunately, in the clinic, the treatment of fungal infections using nystatin and amphotericin B has been hindered by the low selectivity of these molecules for the target cells versus the host cells, poor water solubility and, consequently, low absorption and bioavailability. , In this work, we showed that FsC could serve as an active targeting molecule for these pathogenic fungi (Figure and Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Stimulation of macrophages and neutrophils with mannan resulted in ROS and NO generation, as well 25,26 . Furthermore, mannan induced the release of TNF from dendritic cells 27 . It was demonstrated that mannan increased both the proliferation and the activation of B cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Furthermore, mannan induced the release of TNF from dendritic cells. 27 It was demonstrated that mannan increased both the proliferation and the activation of B cells. 28 Also, mannan promoted or inhibited lymphocyte proliferation as well as it suppressed the phagocyte function of neutrophils and monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The former differentiate into Th1, Th2, and Th17. By secreting IFN-g, IL-4, IL-6, and TGF-b, et al (6)(7)(8), the adaptive immune response is induced to participate in pathogenesis (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…By secreting IFN-γ, IL-4, IL-6, and TGF-β, et al. ( 6 8 ), the adaptive immune response is induced to participate in pathogenesis ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%